2005
DOI: 10.1021/ja052619c
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Strategy to Synthesize Highly Ordered Mesoporous Silicas with Very Large Pores

Abstract: By employing a novel low-temperature synthetic pathway, highly ordered cubic mesoporous materials with hitherto the largest pores (up to 27 nm) and unit cells (up to 44 nm) have been successfully obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
316
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(327 citation statements)
references
References 17 publications
11
316
0
Order By: Relevance
“…Conversely, the absence of FC-4 causes the production of mesoporous silica with micrometer size particles (8À12 μm) as it is the case for standard FDU-12-type materials. 9,29 Nitrogen physisorption results of the sample LP-MSNs (Supporting Information, Figure S1) demonstrate a type IV isotherm with H2 hysteresis loop at high relative pressures indicating the existence of large mesopores with cage-like structures. 29 The pore size was determined using the BroekhoffÀde Boer (BdB) method 30 considering spherical shape pores, although deviation from ideal spherical pore morphology is possible here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the absence of FC-4 causes the production of mesoporous silica with micrometer size particles (8À12 μm) as it is the case for standard FDU-12-type materials. 9,29 Nitrogen physisorption results of the sample LP-MSNs (Supporting Information, Figure S1) demonstrate a type IV isotherm with H2 hysteresis loop at high relative pressures indicating the existence of large mesopores with cage-like structures. 29 The pore size was determined using the BroekhoffÀde Boer (BdB) method 30 considering spherical shape pores, although deviation from ideal spherical pore morphology is possible here.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the usage of low temperature enhances the penetration of the swelling agent TMB (1,3,5-trimethylbenzene) into the hydrophobic core of the micelles during synthesis, which ultimately results in an extra enlargement of pore size (27.9 nm). 15,29,31 The use of high hydrothermal treatment temperature of 140°C contributed in the widening of the entrance pore size above 13.4 nm. Owing to the small spherical particle size and the large pore size (large unit cell), the mesostructure symmetry of the sample is difficult to determine by powder X-ray analysis (XRD).…”
Section: Resultsmentioning
confidence: 99%
“…In order to optimize the dispersion degree and particle size of the benzene-silica hollow nanosphere, KCl was added in the initial mixture because the inorganic salts were always used to adjust the structure and morphology of the mesoporous materials in combination with nonionic copolymer surfactant. 24, 25 The TEM NBSB-423-105 was synthesized using 1,4-bis(trimethoxysilylethyl)benzene (BTSEB) as the silane precursor. To our delight, hollow nanospheres could still be observed in the TEM image of NBSB-423-105, though the contrast between the core and shell is not as clear as that of NES and NBS samples.…”
Section: Synthesis Of Silica Particlesmentioning
confidence: 99%
“…18 Recently, an extra-large pore ordered mesoporous silica FDU-12 with pore size up to 27 nm has been successfully synthesized. 19 Its large pore size and three-dimensional pore connectivity present the material as a superior choice over MCM-41 and SBA-15 for the immobilization of large enzymes, especially with respect to mass transfer and pore blocking. 20 However, previous reports showed that surface functionalization of the silica support materials is necessary prior to enzyme immobilization such that the interaction between the silica surface and enzyme is maximized, and a beneficial microenvironment for optimum catalytic activity of the enzyme is created.…”
Section: Introductionmentioning
confidence: 99%